Integration of μ-SOFC Generator and ZEBRA Batteries for Domestic Application and Comparison with other μ-CHP Technologies. (August 2015) - Antonucci, V.; Brunaccini, G.; De Pascale, A.; Ferraro, M.; Melino, F.; Orlandini, V.; Sergi, F.
Abstract: This study investigates the possibility to integrate a Solide Oxide Fuel Cell (SOFC) prime mover and ZEBRA batteries, with the aim to fulfill a domestic user energy demand and to reduce the primary energy consumption, thereby, to enhance the total efficiency in a μ-CHP (Combined Heat and Power) application on a yearly basis. A realistic operational sequence of the SOFC-ZEBRA integration has been calculated using simple logic conditions. Both electric and thermal integration have been considered, in order to exploit the SOFC residual heat for the battery stand-by feeding. The key advantage of this system architecture is that the SOFC is operated without major load variations close to constant load, resulting in longer lifetime and thus reducing total costs of operation. Eventually, a comparison with alternative μ-CHP technologies has been carried out, highlighting the SOFC-ZEBRA potential.